Positron emission tomography and its role in the assessment of vulnerable plaques in comparison to other imaging modalities - Proaño-Bernal, Leonardo; Gilabert-García, Ana; Sharma-Sharma, Shubhang; Mora-Barrera, Citlali M.; Singer-De-la-Garza, Jethro; Beristain-de-la-Rosa, P. Yael; Basile-Alvarez, Martín Roberto; Guerra, Enrique C.; Bermudez-Gonzalez, Jorge Luis; Luna-Alcala, Santiago; Espinola-Zavaleta, Nilda; Alexanderson-Rosas, Erick (Frontiers in Medicine, 2024)
The diagnosis and management of vulnerable plaques are topics of high interest in the cardiovascular field. Although imaging techniques like computed tomography angiography (MCTA) and ultrasonography (USG) can structurally evaluate atherosclerotic plaques, they are limited in examining internal cellular processes. Positron emission tomography (PET) molecular imaging, on the other hand, can highlight these cellular processes, including inflammation, angiogenesis, and lipid oxidation. Magnetic resonance imaging (MRI) is also a valuable non-invasive imaging technique that can provide detailed anatomical and functional information on the cardiovascular system. In this review, we compare the advantages and drawbacks of MCTA, USG and MRI imaging techniques with PET molecular imaging in evaluating vulnerable plaques. PET imaging allows physicians to measure different pathophysiological events within the plaque using intravenous radiotracers, of which 18F-fluorodeoxyglucose (18F-FDG) is the most validated one. By using 18F-FDG, physicians can understand the formation of the plaque, assess the accumulation of macrophages, and predict major cardiovascular events. However, some limitations exist in using 18F-FDG, including myocardial uptake and low sensitivity in imaging coronary arteries. We also mention other radiotracers that can help in evaluating vulnerable plaques, including 18F-NaF. Although PET imaging is still challenging, it has shown promise in evaluating vulnerable plaques and could be used to intervene in high-risk patients before major cardiovascular events occur.